133 SURGICAL MANAGEMENT OF ESOPHAGEAL STENOSIS DUE TO CORROSIVE SUBSTANCES. (14th September 2020) - Tustumi, F; Seguro, F; Szachnowicz, S; Bianchi, E; Morrell, A; Silva, M; Duarte, A; Sousa, J; Laureano, G; Rocha, J; Sallum, R; Cecconello, I
Abstract: : Corrosive ingestion is a significant challenge for healthcare support. Limited data is available regarding the best treatment, and there is still a lack of consensus about the optimal surgical approach and its outcomes. This study aims to show a single-institution experience of surgical treatment of esophageal stenosis due to corrosive substance ingestion and review the current literature. Methods: A retrospective review, including demographics, psychiatric profile, surgical procedures, and outcomes, is described. A systematic review of the literature was performed in PubMed. Results: In total, 27 surgical procedures for esophageal stenosis due to corrosive substances ingestion were performed from 2010 to 2019. Depression and drug abuse were diagnosed in 30% and 22% of the included patients, respectively. The incidence rate of cancer in patients with corrosive esophageal stenosis is 701.7–874.1 per 1, 000, 000 person-years, and the cancer latency between corrosion ingestion to carcinoma is 10–58 years. Esophagectomy and esophageal bypass were performed in 13 and 14 patients, respectively. No 30-day mortality was recorded. Conclusion: The surgical intervention either by esophagectomy or esophageal bypass seems to show a high success rate. However, the outcomes depend on a high-quality multidisciplinary network of esophageal and thoracic surgeons, intensivists, psychologists, psychiatrists, and nutritional teams.